The Influence of Self-Motivation, Family Environment, Technoprenuership Literacy Through Self-Efficacy on The Interest in Entreprenuership (Journal of Economic Education, 2022)
Entrepreneurship interest is a person’s interest in business activities with creativity to take advantage of opportunities and be able to bear the risks that will be faced without coercion. The purpose of this study was to test whether there is an influence of self-motivation, family environment and technoprenuership literacy through self-efficacy on the interest in entrepreneurship of State Vocational High School students in Semarang Regency. The population in this study were students of State Vocational Schools in Semarang Regency academic year of 2022/2023, totaling 3,501 sample students. The sample was taken using the proportional random sampling technique. It obtained a sample of 170 respondents. The data collection technique in this study used a questionnaire. The data analysis technique that was used is descriptive statistical analysis and path analysis. The results showed that the entrepreneurship interest of State Vocational High School students was in the good category, self-motivation was in the high category, family environment was in the good category, technoprenuership literacy was in the good category, and self-efficacy was in the very good category. The influence of self-motivation, family environment, technoprenuership literacy through self-efficacy mediation variables have a positive and significant effect directly and indirectly on the interest in entrepreneurship of students of State Vocational Schools in Semarang Regency. This research is expected to enrich the body of knowledge and test the Theory of Planned Behavior (TPB) related to entrepreneurship interest and as a basis for policy in the world of education, especially entrepreneurship education in Vocational Schools as a guide in developing entrepreneurship interest. It is recommended to increase students' self-motivation and more intensive self-efficacy.